The influence of proximity induced ferromagnetism, superconductivity and Fermi-velocity on evolution of Berry phase in Bi2Se3 topological insulator. (19th February 2015) - Sengupta, Parijat; Klimeck, Gerhard
Abstract: Bi2 Se3 is a well known 3D-topological insulator (TI) with a non-trivial Berry phase of attributed to the topology of the band structure. The Berry phase shows non-topological deviations from in the presence of a perturbation that destroys time reversal symmetry and gives rise to a quantum system with massive Dirac fermions and finite band gap. Such a band gap opening is achieved on account of the exchange field of a ferromagnet or the intrinsic energy gap of a superconductor that influences the topological insulator surface states by virtue of the proximity effect. In this work the Berry phase of such gapped systems with massive Dirac fermions is considered. Additionally, it is shown that the Berry phase for such a system also depends on the Fermi -velocity of the surface states which can be tuned as a function of the TI film thickness.